Extreme measures. (Economist, 2000)
Focuses on a computer scientist movement called extreme programming (XP), which was invented by software developer Kent Beck. Tenets of XP such as programmers should work in pairs; Skeptics of the computer methodologies of XP; Appeal of XP that has easy-to-maintain code for employers and programmers.